ANALISIS YURIDIS PERATURAN DAERAH TENTANG BANTUAN HUKUM DI KABUPATEN TANAH DATAR PERSPEKTIF SIYASAH DUSTURIYAH - Winna Dwi Setya; Farida Arianti; Bustamin Bustamin (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2022)
The main issues in this thesis are Juridical Analysis of the importance of forming Regional Regulations regarding the provision of Legal Aid to the Poor in Tanah Datar District and Siyasah Dusturriyah's Analysis of the importance of forming Regional Regulations related to Legal Aid to the Poor in Tanah Datar District? The type of research used was field research with a qualitative approach conducted at the Tanah Datar District Office of Social Affairs, the Office of the Legal Aid Institute (LBH) Fiat Justitia Batusangkar, while the technique for collecting data was direct interviews, with Mr AZ (head of the Tanah Datar Social), Mr. YA (head of LBH Fiat Justitia Batusangkar), and Mrs. AH, (Young Expert Legal Analyst for the Tanah Datar District Government), and documentation studies, through library literature such as books, scientific papers, journals, documents, laws, and others. The results of the author's research show that in Tanah Datar there are still very many people who are classified as poor and some of them are caught in legal cases, but not all of the poor who are caught in these legal cases get legal assistance from the government, Constraints in providing legal aid this is an unclear regulation and the lack of budget from local government for organizing legal aid for the poor, this is because Regional Regulation No. 1 of 2021 concerning the Implementation of Social Welfare has not been realized. The type of research used was field research with a qualitative approach conducted at the Tanah Datar District Office of Social Services, the Office of the Legal Aid Institute (LBH) Fiat Justitia Batusangkar, while the technique for collecting data was direct interviews, with Mr. AZ (head of the Tanah Datar Social), Mr. YA (leader of LBH Fiat Justitia Batusangkar), and Mrs. AH, (Young Expert Legal Analyst for the Regional Government of Tanah Datar Regency)